Method of assessment of the efficiency of the communication of operational troop grouping system - Shyshatskyi, A.; Suhak, S.; Tiurnikov, M.; Lyashenko, A.; Bokhno, T.; Bondar, O.; Melnyk, A. (Національний технічний університет "Харківський політехнічний інститут", 2020)
The most distinctive features of military communications systems are the high degree of a priori uncertainty about the operational situation and the small amount of source data for communications planning. In such circumstances, it is important to make the right decision-making appraisal apparatus, which will allow the officials of the system management bodies to be confident in the decisions made. Deciding to build a communications system at any level usually involves defining the purpose of its operation, selecting metrics and justifying the evaluation criteria, synthesizing alternative structures, and finding a rational option for deploying the communications system. The practice of the troops has convincingly shown that in the theory and practice of communications, there is a need to improve the scientific and methodological apparatus, which will meet the current conditions of operation of control systems and provide a more adequate assessment of the effectiveness of deployable communications systems. In this article, the authors propose a method for evaluating the effectiveness of the communication system of the operational troop grouping. The above method is based on the first time use of the communication system accessibility indicator. In the course of this research, the authors used the basic principles of communication theory, noise immunity theory and intelligence. The novelty of the proposed method is that the communication system operational troops grouping are estimated by generalized indicator of availability of channel resources and network communications system of the operational troops grouping. The practical value of the proposed methodology is that the methodology allows for a more accurate assessment of the communications system, the identification of deployment arrangements and measures to improve the effectiveness of the operational troops grouping.

Найбільш характерними особливостями побудови систем зв'язку військового призначення є високий ступінь апріорної невизначеності стосовно оперативної обстановки та малий обсяг вихідних даних для планування зв'язку. У таких умовах важливий правильний вибір апарату оцінки прийнятих управлінських рішень, який дозволить посадовим особам органів управління системою зв’язку бути впевненим у рішеннях, що приймаються. Прийняття рішення на побудову системи зв'язку будь-якого рівня, як правило, включає визначення мети її функціонування, вибір показників і обґрунтування критеріїв оцінки, синтез альтернативних структур і пошук раціонального варіанту розгортання системи зв'язку. Практика військ переконливо показала, що в теорії та практиці організації зв’язку виникла необхідність в удосконаленні науково-методичного апарату, що буде відповідати сучасним умовам функціонування систем управління та забезпечувати більш адекватну оцінку ефективності систем зв’язку, що розгортаються. В зазначеній статті авторами запропоновано методику оцінки ефективності системи зв’язку оперативного угруповання військ. Зазначена методика заснована на використання показника доступності системи зв'язку з першого разу. В ході зазначеного дослідження авторами використані основні положення теорії зв’язку, теорії завадостійкості та розвідзахищеності. Новизна запропонованої методики полягає в тому, що система зв’язку оперативного угруповання військ оцінюється по узагальненому показнику доступності канальних та мережевих ресурсів системи зв'язку оперативного угруповання військ. Практичне значення запропонованої методики полягає в тому, що зазначена методика дозволяє більш точніше оцінити систему зв'язку, визначити заходи щодо розгортання системи зв'язку та виробити заходи стосовно підвищення ефективності системи зв'язку оперативного угруповання військ.
Методика оцінки ефективності системи зв'язку оперативного угруповання військ
Keywords: communication system evaluation; noise immunity; operational troop grouping; intelligence; оцінювання систем зв'язку; завадозахищеність; розвідзахищеність; оперативні угруповання військ